An Analysis of Main Character in Miss Brill Short Story by Katherine Mansfield: A Psychological Approach - Eka Wilany (English Department, University of Riau Kepulauan, Batam,Indonesia, 2015)
The objective of this research was to describe the psychological approach of main character in Miss Brill short story by Katherine Mansfield. The result of the research was analyzed by using Freud Theory about Id, Ego, and Superego. Based on the result, the main character Miss Brill has a strange behavior that is only for attracting the people around her. She can not ignore her subconscious. She looked like happy but in fact she felt lonely. She wanted to be respected and loved by people around her and has relationship with someone. Moreover, she is an independent woman who feels lonely. Id that influences it is the happiness or willingness to get a present from someone special; she is unaware that she needs it. However, because of her loneliness Miss Brill never thinks about it. It is influenced by the superego. The superego can be understood as reflection of Miss Brill loneliness and her willingness to have relationship with other in her life. The individual Ego can differentiate itself from surroundings; it combines to form the core of the personality. Ego controls the direction of action, deciding which one will be satisfied. Characteristics do not change by the time. Moreover, the superego is the moral aspect accordance with the norms of society. It is suggested for the next researcher might be maximize the literary study for this short story to another approach. Key Words: Psychological Approach; Id; Ego;and Superego